IMPLEMENTATION OF CURRICULUM IN SCHOOLS: MONITORING AND SUPERVISION - Nikodemus Saung Poleallo; Mesta Limbong; Dameria Sinaga (RADJA PUBLIKA, 2025)
Curriculum implementation in schools is a complex process that requires a systematic approach to ensure that educational goals are effectively achieved. One crucial aspect of this process is monitoring and supervision, which serve as oversight and support mechanisms for teachers and school staff. Monitoring involves continuous observation and data collection on curriculum implementation, while supervision focuses on providing guidance and evaluation to teachers to improve the quality of their teaching. This article examines various effective monitoring and supervision methods, including classroom observations, surveys and questionnaires, as well as clinical supervision and peer review. This analysis demonstrates that systematic monitoring can help identify weaknesses and problems in curriculum implementation early, enabling schools to take timely corrective action. Furthermore, supervision that focuses on teachers' professional development can enhance their teaching skills and motivation, which in turn contributes to improving the quality of learning for students. This article also identifies key challenges in implementing monitoring and supervision, such as resource constraints and resistance to change. By presenting case studies and best practices from various schools, this article offers practical recommendations for overcoming these challenges and improving the effectiveness of monitoring and supervision.